2009
DOI: 10.1016/j.jpsychores.2009.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of Tourette syndrome: A review

Abstract: Objectives-This paper summarizes and evaluates recent advances in the genetics of Gilles de la Tourette Syndrome (GTS).Methods-This is a review of recent literature focusing on: 1) the genetic etiology of GTS; 2) common genetic components of GTS, Attention Deficit Hyperactivity Disorder (ADHD), and Obsessive Compulsive Disorder (OCD); 3) recent linkage studies of GTS; 4) chromosomal translocations in GTS; and 5) candidate gene studies.Results-Family, twin and segregation studies provide strong evidence for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(113 citation statements)
references
References 150 publications
2
110
1
Order By: Relevance
“…Despite these reports, the precise pattern of transmission and the specific genes involved remain elusive. Linkage analyses have suggested several chromosomal locations, but without a clear reproducible locus (Pauls, 2006;O'Rourke et al, 2009). Similarly, candidate gene studies have failed to yield consistent results for specific susceptibility genes.…”
Section: Etiologymentioning
confidence: 99%
“…Despite these reports, the precise pattern of transmission and the specific genes involved remain elusive. Linkage analyses have suggested several chromosomal locations, but without a clear reproducible locus (Pauls, 2006;O'Rourke et al, 2009). Similarly, candidate gene studies have failed to yield consistent results for specific susceptibility genes.…”
Section: Etiologymentioning
confidence: 99%
“…The definitive etiology of TS is unknown but there is a universal agreement about the strong genetic vulnerability for the disorder with some environmental factors that may play a role in the expression of its severity [9]. The reported case was the first born to a first cousin consanguineous parents (paterno-paternal), nevertheless there were no similar cases in his family or an exposure to a predisposing environmental factor before the development of TS symptomatology.…”
Section: Discussionmentioning
confidence: 95%
“…Some TS cases were reported to act like those suffering from autosomal dominant disorders with 50% chance to transmit the mutant gene(s) to their offspring but whether the mutant gene(s) will be expressed or not and to what extent and form is greatly variable (variable expression and incomplete penetrance). In addition, it was found that gender plays a role in gene expression in cases of TS as males are more likely to manifest tics than females [14,15].…”
Section: What Is Behind the Occurrence Of Tourette Syndrome?mentioning
confidence: 99%